A GLANCE OF ACADEMıC AND SOCIAL LIVES: THE TOUGHTS OF MOTHER RESEARCH ASSISTANTS - Ayşe KAZANCI TINMAZ (Fırat University, 2019)
The aim of this study is to investigate the views of mother research assistants about academic and social lives. The research was carried out according to the phenomenon pattern of qualitative research methods. The study group consisted of 11 mother research assistants determined by criterion sampling. The data were collected by a semi-structured interview form developed by the researchers and analyzed by descriptive analysis technique. Some of the findings are as follows: Participants stated that academic studies do not delay the age of marriage, however, that they had children at the time they considered themselves suitable for having children professionally. The participants stated that the real responsibility and burden are on their own, even if they get help from their spouses in terms of their home responsibilities. Mother research assistants stated that it was very difficult to find a caretaker. They did not see any positive discrimination because they were mothers in their working lives. Mother research assistants have some difficulties in academic and social lives. Some of them are; inability to study at home, slow progress of academic studies, not being able to participate in scientific activities such as congress, conference, sleep less and that do not have time for themselves and their family etc. Participants think that male research assistants carry out their academic studies more quickly and comfortable. It was stated that being a research assistant had a positive effect on the relationship with the child and his/her education in general. Participants choose their profession as their “ideals” and they have a positive attitude towards their profession. Participants have some difficulties due to maternity but they enjoy their profession. According to them, it is a respectable profession, but a stressful profession with a shortage of staff. According to the findings obtained in the research, some suggestions were made.